“The Great Transformation” and Suicide: Local and Long-Lasting Effects of 1930 Bank Suspensions - Baller, Robert D.; Levchak, Phil; Schultz, Mark (Suicide and Life-Threatening Behavior, 2010)
Depression-era bank suspensions and failures are conceptualized as products of the first part of what Polanyi (1994) called “The Great Transformation,” which involved an imbalanced institutional arrangement in which the economy dominated other institutions. Relying on Durkheim (1897/1951) and Merton (1938, 1968), it is argued that these banking problems accentuated the type of chronic anomie that Durkheim theorized would create normative deregulation and elevated suicide rates over the long-term. Results from county-level analyses are supportive as the 1930 bank suspension rate is positively related to the 2000 suicide rate, controlling for contemporary and historical factors. The mediating roles of integration and chronic anomie are considered, with the latter measured using data from the geocoded General Social Survey.
Sociology
Keywords: DURKHEIM; Emile; MERTON; Robert; The Great Depression; anomie; countermovement; suicide; suicidology

'False' Optimism: The Key to Historic Breakthroughs? A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Clawson, Dan (Global Labour Journal, 2010)
Sociology
Keywords: BURAWOY; Michael; borderline; global labor studies; global labour studies

From Critical Sociology to Combat Sport? A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Webster, Edward (Global Labour Journal, 2010)
Sociology
Keywords: BURAWOY; Michael; double movement; global labour studies; globalization

Karl Polanyi e a Nova Sociologia Económica: Notas sobre o conceito de (dis)embeddedness - Machado, Nuno Miguel Cardoso (Revista Crítica de Ciências Sociais, 2010)
No contexto da Nova Sociologia Económica, Karl Polanyi é quase consensualmente considerado o “pai” do conceito de incrustação (embeddedness). Todavia, este conceito foi alvo de uma apropriação selectiva por parte da disciplina, sendo negligenciada a sua relação com o restante edifício teórico construído por Polanyi. Pode, com efeito, falar‑se de uma “grande transformação” sofrida pelo conceito de incrustação: se em Polanyi ele está associado a um nível macro(económico) e é utilizado para evidenciar o carácter excepcional da economia capitalista de mercado – que se encontra desincrustada da sociedade –, na NSE, por seu turno, é normalmente associado a um nível meso (e até micro), sendo preconizado que todas as economias – incluindo a capitalista – estão incrustadas. ENG translation: Within the context of New Economic Sociology, Karl Polanyi is almost universally considered the “father” of the concept of embeddedness. However, this concept has been subject to selective appropriation by this discipline and its relationship to the remaining theoretical edifice constructed by Polanyi has been neglected. It is, in fact, possible to refer to the “great transformation” to which the concept of embeddedness has been subjected: whereas in Polanyi’s work it is associated with the macro(economic) level and is used as evidence of the exceptional nature of the capitalist market economy – disembedded from society – in NES, it is normally associated with the meso (and even micro) level, on the assumption that all economies – including capitalist economies – are embedded.
Sociology
Keywords: Karl Polanyi; Nova Sociologia Económica; capitalismo; economia de mercado; economic sociology; embeddedness; incrustação

Decommodification and Egalitarian Political Economy - Vail, John (Politics & Society, 2010)
This article contends that decommodification is an appropriate concept for understanding diverse initiatives such as fair trade, microfinance, open source, social enterprises, and the environmental commons as component features of a common process. Decommodification is conceived as any political, social, or cultural process that reduces the scope and influence of the market in everyday life. Given recent transformations in market societies, a more expansive framework for decommodification is urgently required. Decommodification would insulate non-market spheres from market encroachments; increase the provision of public goods and expand social protection; promote democratic control over the market by creating economic circuits grounded in a logic predicated on social needs rather than profit; and undermine market hegemony by revealing the market’s true social costs and consequences. By ensuring basic needs, enhancing individual capacities and capabilities, and promoting social cooperation and collaboration, decommodification constitutes a central feature of an egalitarian agenda.
Sociology
Keywords: decommodification; double movement; icy silence; sociology

From Polanyi to Pollyanna: The False Optimism of Global Labor Studies - Burawoy, Michael (Global Labour Journal, 2010)
Sociology
Keywords: EVANS; Peter; 1944-; MARX; Karl; 1818-1883; counter-hegemonic globalization; critique; labor studies; labour studies

The Aporia of Power: Crisis and the Emergence of the Corporate State - Kapferer, Bruce (Social Analysis, 2010)
The argument focuses on the corporate state as an increasingly significant political assemblage that has enabled new configurations of power with related social effects. Here the discussion proceeds from Karl Polanyi's thesis in The Great Transformation. A critical idea that Polanyi pursued related to the state production of economism and individualism, which prepared the ground for the expansion of capital in its globalizing form. The essay develops this idea, indicating that the nationalist capitalism of the state led to a radical change in the political and social orders of states, gradually giving rise to the corporate state assemblage. The emphasis here is on the corporate state as a socio-political order that places radically distinct structural dynamics into impossible conjunction, leading to progressively disastrous social effects concerning poverty and the emergence of new configurations in which war and violence take specific shapes.
Anthropology; Sociology
Keywords: Great Transformation; The (Book); bureaucratic processes; corporate state; crisis; economism; globalization; individualism; nation-state; poverty; power (social sciences); reterritorialization; violence; war; war machine

The Idea of a Three-Dimensional Conflicts Law as Constitutional Form - Joerges, Christian (Social Science Research Network, 2010)
‘Constitutionalisation’ is the key concept in the search for legitimate governance in the European Union and in the international system. This paper suggests the revitalising of a discipline which is widely neglected in European law and international law scholarship. It does not, however, recommend a return to the conflict of laws (private international law) in the traditional sense. The new type of conflicts law that the paper advocates is not concerned with selecting the proper legal system in cases with connections to various jurisdictions. This conflicts law is conceptualised as a response to the increasing inter-dependence of formerly more autonomous legal orders and to the democracy failure of constitutional states which result from the external effects of their laws and legal decisions on foreign systems and on their citizens who cannot understand themselves as their authors. European law has a vocation and many means both to compensate for the democracy failures of member states and to build upon this potential in its constitutionalisation. The conflicts law approach also provides new, albeit more restrained, perspectives at international level. WTO law is used to explore and document its constitutional perspectives. The conflicts law approach is differentiated into three dimensions. With this differentiated fabric, the approach responds to transformation processes which have affected contemporary law at all levels of governance after the rise of regulatory politics and the turn to governance. In its second dimension, conflicts law seeks to constitutionalise co-operative problem-solving under the lead of administrative bodies, while its third dimensions is concerned with both the recognition and the supervision of transnational governance arrangements and para-legal regimes.
Law; Sociology
Keywords: BLOCK; Fred; Europeanisation; World Trade Organization (WTO); always socially embedded' economy; constitutionalisation; deliberative democracy; economic law; economic sociology; multilevel governance; private international law; rule of law; social embeddedness; social regulation; supranationalism

Decency in Anglo-American Financial Centres? - Pixley, Jocelyn (Thesis Eleven, 2010)
How can a partial, revisable utopia of 'decent society' be used as a yardstick for assessing today's impersonal forms of social integration? In economic life - this essay's focus - Polanyi's hopes that the 'economic system' might cease 'to lay down the law to society' is a start. Recently, financial firms sold commodified promises and obligations on the allure of democratizing credit and providing financial 'choice' to millions. Yet these 'civilities' exploited people's hopes for a dignified life. Any new, partial utopia (as Keynes's was too - to remove the egregious, humiliating features of 'the society in which we live') is yet to be devised. Maria Markus's concept is useful to ask whether the instrumentalism of macro-economic concepts is a distortion of the institutions of money or intrinsic to them. Could solidaristic compromises through civil society minimize disrespectful relationships embedded in money to create decent institutions?
Sociology
Keywords: MARKUS; Maria; POLANYI; Karl; 1886-1964; decent economic institutions; economic democracy; economic systems; embeddedness; essay (literary form); financial centres; social integration; utopias

Cultural political economy and critical policy studies - Jessop, Bob (Critical Policy Studies, 2010)
This article introduces cultural political economy as a distinctive approach in the social sciences, including policy studies. The version presented here combines critical semiotic analysis and critical political economy. It grounds its approach to both in the practical necessities of complexity reduction and the role of meaning-making and structuration in turning unstructured into structured complexity as a basis for ‘going on’ in the world. It explores both semiosis and structuration in terms of the evolutionary mechanisms of variation, selection, and retention and, in this context, also highlights the role of specific forms of agency and specific technologies. These general propositions are illustrated from ‘economic imaginaries’ (other types of imaginary could have been examined) and their relevance to economic policy. Brief comments on crisis-interpretation and crisis-management give this example some substance. The conclusion notes some implications for research in critical policy studies.
Sociology; Political Science
Keywords: complexity; crisis; crisis-management; cultural political economy; cultural turn; finance-led accumulation; green new deal; neoliberalism

Globalization, Crisis and Social Transformation: A View from the South - Munck, Ronaldo (Globalizations, 2010)
The dominant narrative around the unfolding capitalist crisis is firmly focused on the dominant economies, and in particular the US. This is understandable given that the proximate causes of the crisis lie in the imperial heartlands and crisis resolution measures taken there will have a global impact. But a 'view from the South' is needed to redress the balance and prevent the decimation of global majority likelihoods being presented as mere collateral damage. The first section below tackles the crisis from a global (globalization) perspective emphasizing its impact in the South and what that it might mean in terms of political prospects. I then go on to develop a hybrid Karl Polanyi/Antonio Gramsci theoretical lens on counter-movements based on their writings responding to the last systemic capitalist crisis in the 1930s. Finally, I turn to the ways in which the international labour movement and the subaltern or post-colonial worlds are contesting the terrain vacated by unregulated market capitalism. As Gramsci would say the old is dying but the new has not yet been born. La narrativa dominante alrededor de la crisis capitalista revelada, esta firmemente enfocada a las economias dominantes, y particularmente E.E.U.U. Esto es comprensible, dado que las proximas causas de la crisis yacen en la region central imperial y las medidas de resolucion de la crisis que se tomaron alli tendran un impacto global. Pero se necesita un 'punto de vista desde el sur' para compensar el equilibrio y prevenir la devastacion de las posibilidades de las mayorias globales presentadas como simple dano colateral. La primera seccion abajo trata la crisis desde una perspectiva global (globalizacion), enfatizando su impacto en el sur y lo que eso puede significar en terminos de prospectos politicos. Luego procedo con el desarrollo de una lente teorica hibrida de Karl Polanyi/Antonio Gramsci sobre movimientos opuestos en base a sus escritos que responden a la ultima crisis capitalista sistemica en la decada de 1930. Finalmente, vuelvo a las maneras en las cuales el movimiento laboral internacional y los mundos subalternos o postcoloniales estan disputando el terreno vacio por el mercado capitalista sin regulacion. Como Gramsci diria, lo viejo se esta muriendo, pero lo nuevo no esta aun por nacer. [image omitted]
Sociology; Political Science
Keywords: GRAMSCI; Antonio; 1891-1937; South; capitalism; countermovement; crisis; financial crises; financial crisis; globalization; hegemony; international markets; labour; post-colonial; social change; transformation

A British Bureaucratic Revolution? Autonomy Without Control, or "Freer Markets, More Rules." - Le Galès, Patrick; Scott, Alan (Revue Française de Sociologie, 2010)
This paper addresses a puzzle: how to account for changes in the routine behavior of groups, organizations and individuals in Britain? Following a detailed analysis of state-market interdependence and the role of the state in creating the market, an analysis drawn from the thinking of Weber and Polanyi, we suggest adapting Weber's notion of bureaucratic revolution: in what we call the British bureaucratic revolution, the state has played an essential role in social change by creating institutions and rules that are lastingly reorienting actors' behavior. The example of the healthcare field is examined in order to identify the specific mechanisms that have been impacting on behavior within an approximately ten-year period; namely, the introduction of 1) competitive practices (sanction/reward) and 2) auditing and inspection. If this interpretation is valid, then it is reasonable to assume that the effects of this bureaucratic revolution extend beyond Britain.
Sociology
Keywords: Great Britain; bureaucracy; medical care; revolutions; social change

Work After Globalization: Building Occupational Citizenship - Standing, Guy (Edward Elgar Publishing, 2010)
Per Google Books: This is a scholarly and erudite work. . . There is a wealth of detail, all illustrated with plenty of fascinating examples. . . It is impossible to give the full flavour of this thoughtful and stimulating book in even a long review, but it deserves to be
Sociology; Political Science
Keywords: business & economics - labor; business & economics - labour; embeddedness; industrial citizenship; political science / labor & industrial relations; political science / labour & industrial relations; social science / sociology / general

The Making of Karl Polanyi's Economic Sociology. (In Japanese. With English summary.) - Wakamori, Midori (History of Economic Thought, 2010)
The main purpose of this paper is to understand Polanyi's research project after The Great Transformation. This includes his developing ideas on economic history and theory of economic institutions after 1947, when he came to Columbia University in New York. This paper deals mainly with Polanyi's new agenda, namely "the place of the economy in society" in the intellectual context of post World War II United States of America.
Economics; Sociology
Keywords: Marxist; Sraffian; economic anthropology; economic sociology; history of economic thought since 1925: socialist; history of economic thought: individuals; social and economic stratification

Social Economy and the fight against Social Exclusion: Preliminary remarks with reference to the Greek welfare state - Adam, Sofia (2010)
Recent academic discourse and European social policies highlight the (potential) effectiveness of social economy practices as a means to address social exclusion especially for the more disadvantaged social groups. Apart from terminological debates on the aforementioned troubled concepts, fundamental questions needs to be examined: To what extent social economy practices flourish as a result of policy shifts towards further commercialization of public social services or to what extent do they emerge from bottom up collective survival strategies? This paper attempts to address this question with reference to the political economy of the Greek welfare state.
Keywords: Greece; economic sociology; embeddness; political economy; social economy; substantive approach; welfare state

Au-dela de la dichotomie marche-institutions: L'institutionnalisme de Douglass North face au defi de Karl Polanyi. (With English summary.) - Didry, Claude; Vincensini, Caroline (Revue Francaise de Socio-economie, 2010)
On the basis of the "challenge" North (1977) identified in the works of Polanyi, we propose to outline the originality of North's institutionalism, especially in comparison with "new institutionalism" in economics as well as in sociology. Far from endorsing the dichotomy between market and non market dimensions of economic activities at the basis of the analyses of Williamson and Granovetter, North's definition of institutions as "rules of the game" allows him to conceive of institutions as the institutional foundations of the market and therefore as explanatory principles of historical dynamics.
Sociology
Keywords: Austrian; current heterodox approaches: institutional; evolutionary; history of economic thought; history of economic thought since 1925; institutional

The ordering of change: Polanyi, Schumpeter and the nature of the market mechanism - Harvey, Mark; Metcalfe, Stan (Markets, Rules and Institutions of Exchange, 2010)
Sociology
Keywords: SCHUMPETER; Joseph Alois; 1883-1950; market mechanism

Fair Trade and the Double Movement: The Promise and Contradictions of Improving Labor Standards in the Global South via Market Mechanisms - Shorette, Kristen (Journal of Workplace Rights, 2010)
I examine Fair Trade (FT) as a social movement that emerges as a regulative force in response to the rise of neoliberalism. I apply Polanyi's (1944, 1957) classic concepts of embeddedness and the double movement to understand the conflict that arises within a coherently motivated social movement. Using interview and participant observation data along with content analysis of FT organization mission statements, this research examines the role of conflict within the FT movement over how best to improve the well-being of producers in the global South. I discuss the different, conflicting ways in which FT participants think about improving labor conditions in the global South and the inherent conflict in using market mechanisms to counter market forces. I conclude that while participants share the values of human rights, equality, and environmentalism, realizing these goals through concrete market activities reveals the tension between the benefits of liberalizing and the benefits of regulating the production and sale of FT goods that may impede the continued growth of the movement.
Sociology
Keywords: developing countries; double movement; embeddedness; fair trade; human rights; labor laws & legislation; labour laws & legislation; neoliberalism; production standards; social movements; unfair competition; workplace rights

Local Food: A Social Movement? - Starr, Amory (Cultural Studies/Critical Methodologies, 2010)
This article analyzes the development of “local food” institutions from a social movements perspective. Over the last decade, institutions that “shorten the links” between producer and consumer have developed through a diverse collaboration of many social sectors (farmers, agronomic experts, retailers, chefs, food writers, and several distinct consumer sectors). Some agronomists and rural sociologists critical of the globalization and industrialization of agriculture have recognized this development as heralding Polanyian “reembedding” of market exchanges in social relations. This article analyzes whether and how local food is a social movement, using new social movement theory as an analytic framework.
Sociology; Cultural Studies
Keywords: community-based economics; local food; local foods; localism; organic food; organic foods; social change; social movements; social psychology

The Role of the State in Making a National Market: The Evolution of the Grain Market in China (1978-2000) - Zhou, Wubiao (China Agricultural Economic Review, 2010)
The paper aims to examine Karl Polanyi's view of market evolution in the context of the emergence of a national grain market in China's transition economy. The dataset used includes information about inter-provincial grain trade on China's grain market from November 1999 to October 2000. A priori blockmodelling method is used for hypothesis testing. This paper finds that a partially integrated national grain market had emerged at the beginning of the twenty-first century in China in spite of local protectionism. Additionally, the emergence of this market is found to be partly a result of the reform-oriented state's attempt to create national wholesale grain markets.
Economics; Sociology
Keywords: agricultural policy; agriculture; agriculture: aggregate supply and demand analysis; collectives; communes; economic development: agriculture; energy; environment; food policy; natural resources; other primary products; prices